Evaluation on absenteeism effect in production line at aircraft composite manufacturer - Mat Desa, W.L.H. (Penerbit UTM Press, 2015)
This paper studies the effect of absenteeism in production line. The analysis shows that the number of absentees at production line increases the workload to the available worker and gives effect to the production. Thus, it gives a major potential for generating bottlenecks. To mitigate this problem and ensure that the workload of workers is at optimum level, an appropriate number of production plans need to be investigated. This paper demonstrates the integration of Discrete Event Simulation (DES) and System Dynamics (SD) in simulating the effect of absenteeism in production flow at an aircraft composite manufacturing factory. Based on the preliminary result, the effect of the absenteeism is found to influence the amount of throughput, waiting and cycle time. Â© 2015 Penerbit UTM Press. All rights reserved.